2021
DOI: 10.1002/edm2.293
|View full text |Cite
|
Sign up to set email alerts
|

Yield and costs of molecular diagnostics on thyroid cytology slides in the Netherlands, adapting the Bethesda classification

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
(143 reference statements)
0
6
0
Order By: Relevance
“… 36 This may guide treatment decisions, for example, in the context of de-escalation strategies or directing toward initial total thyroidectomy when a high-risk alteration is found (e.g., ALK , PIK3CA , NTRK fusion, TP53 + RAS , or BRAF V600E + TERT ). 4 , 31 , 36 , 37 A minority of the alterations observed in this study were high risk, confining this benefit as well as the PPV of MD in Bethesda III/IV populations. Other therapeutic advantages, such as those regarding targeted therapies for advanced-stage thyroid carcinoma, are likely more confined for preoperative MD as they only apply to the limited number of patients that develop iodine-refractory disease.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“… 36 This may guide treatment decisions, for example, in the context of de-escalation strategies or directing toward initial total thyroidectomy when a high-risk alteration is found (e.g., ALK , PIK3CA , NTRK fusion, TP53 + RAS , or BRAF V600E + TERT ). 4 , 31 , 36 , 37 A minority of the alterations observed in this study were high risk, confining this benefit as well as the PPV of MD in Bethesda III/IV populations. Other therapeutic advantages, such as those regarding targeted therapies for advanced-stage thyroid carcinoma, are likely more confined for preoperative MD as they only apply to the limited number of patients that develop iodine-refractory disease.…”
Section: Discussionmentioning
confidence: 57%
“…As previously described, the custom Ampliseq™ Cancer Hotspot v6 panel (Thermo Fisher Scientific, Waltham, MA), which targets 87 genes that are relevant for the characterization of thyroid neoplasms, and the Archer ® FusionPlex CTL v2 panel (ArcherDX Inc., Boulder, CO), which assesses 19 relevant genes, were used for somatic mutation and gene fusion analysis, respectively (details provided in the Supplementary Data ). 4 , 25–27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] The utility of comprehensive next-generation sequencing analysis in the context of equivocal Bethesda category III (B-III) lesions has been validated and a recent report suggested that the use of molecular testing may prevent repeat cytology testing and unnecessary surgery. 5 Many pathology laboratories have not implemented these multi-gene platforms in their daily clinical work-up of thyroid nodules yet due to logistical challenges and/or affordability. In this aspect, single-gene analyses of cytology material have proven a cost-effective substitute that increases the diagnostic accuracy of thyroid lesions, including BRAF V600E and TERT promoter mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Combining FNAC with molecular analyses has proven particularly useful for subsets of challenging cases in which standard reporting is not always sufficient to pinpoint malignant cases preoperatively 2–4 . The utility of comprehensive next‐generation sequencing analysis in the context of equivocal Bethesda category III (B‐III) lesions has been validated and a recent report suggested that the use of molecular testing may prevent repeat cytology testing and unnecessary surgery 5 . Many pathology laboratories have not implemented these multi‐gene platforms in their daily clinical work‐up of thyroid nodules yet due to logistical challenges and/or affordability.…”
Section: Introductionmentioning
confidence: 99%